A service position model of package tour services based on the hybrid MCDM approach. Issue 20 (14th December 2019) - Lin, Chia-Li; Kuo, Chung-Ling
ABSTRACT: Traditionally, package tour (PT) agencies assumed that tourists only pay attention to the PT's price, so PT service providers often offer limited package tours based on options and prices. Nowadays, PT service providers face the difficult challenge of how to offer diverse PTs to satisfy tourists' needs based on a reasonable price. This study proposes an evaluation model of package tours based on diverse resources and transportation means. This study proposes a two-dimensional evaluation framework to analyse tourists' needs regarding package tour services and the proposed model could be applied to plan mass customized package tours based on the portfolio of value satisfaction index (VSI) and the price satisfaction index (PSI). The study also proposes that mass customized package tours can improve the traditional tour planning method through a portfolio of diverse tourism resources. Moreover, the study integrates the different choices of traffic and transportation tools, as well as tourism resources and providers in six portfolios of package tours in the Nantou county of Taiwan. These six package tours can be planned through three traffic and transportation tools (tourist coach, railroad, and minibus) and four tourism resources (natural experiences, cultural exploration, shopping and cuisine, and event participation).